The Random Walk Hypothesis for Asean Stock Markets - Pan, Qi Qi (2014)
The objective of this paper is to examine whether stock markets follow a random walk in nine selected ASEAN stock markets namely: FTSE Bursa Malaysia Kuala Lumpur Composite Index (KLCO), Stock Exchange of Thailand Index (SET), Philippines Composite Index (PSEI), Jakarta Stock Exchange Composite Index (JCI), FTSE Straits Times Index (STI), Vietnam Stock Index (VN Index), Hanoi Exchange Index (HNX, Laos Stock Exchange Composite Index (LSX) and Cambodia Securities Exchange Index (CSX). The data consist of three kinds of market prices including daily, weekly, and monthly ones. Data are collected from DataStream and official websites of the indices. Log returns of stocks are used for this study. Four kinds of test are used in this study including serial correlation, runs test, and unit root tests. The research suggests that for Malaysia, Thailand, Philippines, Indonesia, Singapore, Vietnam and Laos, their markets follow a random walk during their testing period, and thus investors cannot get abnormal returns in these markets. But for Cambodia, this research suggests that the market is inefficient.